A dynamic lithium-ion battery model considering the effects of temperature and capacity fading - Erdinc, O.; Vural, B.; Uzunoglu, M. (IEEE, 2009)
Battery models capture the characteristics of real-life batteries, and can be used to predict their behavior under various operating conditions. In this paper, a dynamic model of lithium-ion battery has been developed with MATLAB/Simulink (R) in order to investigate the output characteristics of lithium-ion batteries. Dynamic simulations are carried out, including the observation of the changes in battery terminal output voltage under different charging/discharging, temperature and cycling conditions, and the simulation results are compared with the results obtained from several recent studies. The simulation studies are presented for manifesting that the model is effective and operational.
Keywords: Lithium-ion battery; dynamic model; temperature effect; capacity fading; SIMULATION; SYSTEM; CELLS; FADE; Engineering